Mercados tradicionales minoristas en Lisboa: el camino para la rehabilitación y la gentrificación - Guimarães, Pedro (2020)
After several decades of decline, traditional retail markets are currently under rehabilitation in a wide array of countries. Being important retail spaces for the supply of the local population, especially the fringes with lower income, the divestment of local authorities in these retail precincts fostered their decline. This evolution produced a significant rent gap, attractive for the investment of private developers, which, ultimately, is culminating in the gentrification of several markets worldwide. In this chapter, we analyze how this process is unfolding in Lisbon. The rehabilitation of markets in Lisbon is currently ongoing and two main strategies have been privileged: the supermarket and the food court strategy. Under these strategies, retail gentrification manifests itself in different ways in the rehabilitated markets, causing the direct or indirect displacement of traditional vendors and the change in the traded products, which are detrimental for the local population and its capacity to supply in these retail spaces.